Design of a pump-turbine using a quasi-potential flow approach, mathematical optimization and CFD. Issue 7 (March 2019) - Pochylý, F; Rudolf, P; Štefan, D; Moravec, P; Stejskal, J; Skoták, A
Abstract: Design of a pump turbine ( ns = 135) is carried out using a very fast quasi-potential flow approach for the preliminary design. Theory behind this novel method is presented and its advantages discussed. Further finetuning is performed by coupling of CFD (ANSYS CFX) and particle swarm optimization method. The final design features suppression of the vortex rope over relatively wide turbine operating range. Simulations are verified by model testing in hydraulic laboratory.